(untitled) (Bangladesh Journal of Zoology, 2016)
Spatial and temporal distribution of zooplankton biomass in the Merbok estuary were studied. Zooplankton samples were collected monthly from January to December 2011 at six sampling stations along the river stretch by using 0.13 m diameter plankton net (150 ?m mesh size) in horizontal towing. Average zooplankton biomass ranged from 0.1143 to 1.8217 g dry wt.m-3. The maximum and minimum zooplankton biomass recorded in February and October 2011, respectively. The highest zooplankton biomass was found at Station 6 (downstream) and the lowest in Station 1 (upstream). Zooplankton biomass varied from upstream to downstream. Kruskal-Wallis H test showed that distribution of zooplankton biomass among the sampling months was significantly different (p < 0.05). Spearmans rank correlation analysis revealed significant correlation among zooplankton biomass, chl a concentration and nutrients (p < 0·01). Bangladesh J. Zool. 44(1): 147-152, 2016